Detection of hypermethylation of the p16(INK4A) gene promoter in chronic hepatitis and cirrhosis associated with hepatitis B or C virus - Kaneto, H; Sasaki, S; Yamamoto, H; Itoh, F; Toyota, M; Suzuki, H; Ozeki, I; Iwata, N; Ohmura, T; Satoh, T; Karino, Y; Toyota, J; et al. (Gut, 2001)
Inactivation of the p16(INK4A) (p16) tumour suppressor gene by promoter region hypermethylation has been demonstrated not only in many types of tumours, including hepatocellular carcinoma (HCC), but also in early preneoplastic lesions in the lung, colon, oesophagus, and pancreas. The aim of this study was to examine the methylation status of the p16 promoter in pre- and/or non-neoplastic liver diseases. PATIENTS/SUBJECTS/METHODS: The methylation status of p16 was evaluated in 22 HCC, 17 cirrhosis, 17 chronic hepatitis, nine primary biliary cirrhosis (PBC), eight autoimmune hepatitis, seven drug induced liver disease, six fatty liver, and three normal liver tissues using methylation specific polymerase chain reaction (MSP). p16 protein expression was also examined by immunohistochemical staining. Methylation of the p16 promoter was detected in HCC (72.7%, 16/22) and also in cirrhosis (29.4%, 5/17) and chronic hepatitis (23.5%, 4/17), all of which were positive for hepatitis B or C virus infections. Methylation was not detected in any of the other samples. All methylation positive HCC, cirrhosis, and chronic hepatitis samples showed loss of p16 expression, and a significant correlation was found between methylation and loss of expression. Analysis of serial samples from individual patients with methylation positive HCC revealed that loss of p16 expression with promoter methylation occurred in 18 of 20 patients at the stage of chronic hepatitis without clinically detectable carcinoma. Our results suggest that methylation of the p16 promoter and the resulting loss of p16 protein expression are early events in a subset of hepatocarcinogenesis and that their detection is useful in the follow up of patients with a high risk of developing HCC, such as those with hepatitis B or C viral infections.